DNA markers for eating quality of indica rice in Indonesia. Issue 1 (4th December 2014) - Lestari, Puji; Jiang, Wenzhu; Chu, Sang‐Ho; Reflinur,; Sutrisno,; Kusbiantoro, Bram; Kim, Backki; Piao, Rihua; Cho, Young‐Chan; Luo, Zhixiang; Chin, Joong‐Hyeon; Koh, Hee‐Jong; et al.
Abstract Rice eating quality is considered to be one of the top priorities in determining the agronomical value of rice; thus, the rapid evaluation of eating quality at early breeding generations in breeding programmes for better eating quality is of great importance. In an attempt to develop DNA markers associated with eating quality of indica rice, we used multiple regression analysis to test 54 markers, which were preselected for their possible association with eating quality, using 24 indica varieties with different palatability scores. Of these markers, eighteen markers were found to be significantly associated with palatability according to sensory evaluation. Accordingly, a marker set in the model regression equation with a high R2 (0.997) was formulated to estimate indica rice palatability. Validation suggests that markers and the statistical parameters formulated by the equation could be a potential tool to predict the palatability of cooked Indonesian indica rice and could be reliable in developing country‐dependent model equations for eating quality.